PREPARASI CONTOH UNTUK ANALISIS ASAM AMINO OARI BERBAGAI BAHANBERPROTEIN - Sumardi Sumardi (Jurnal Kimia Terapan Indonesia, 1995)
analysis results are discussed. The hydrolysis methods elaborated in this paper includes: (i) The use of 6N hydrochloric acid solution at 110 and 145°C for the analysis of most amino acids. (ii) The use of 6N hydrochloric acid solution after pre-hydro-lysis oxidation procedure using performic acid for methionine and cystine determination; (iii) The use of sodium hydroxide or barium hydroxide solutions for tryptophan determination. Both precision and accuracy of the analytical data resulted from the application of those hydrolysis methods are also discussed. It may be concluded that in order to be able to determine all of the amino acids in the sample, more than one hydrolysis procedure or sample preparation method have to be used.